Only sequence at your peril: examining assumptions of soil microbial ecology in the monitoring of ecological restoration - Hart, Miranda; Cross, Adam; D'Agui, Haylee; Dixon, Kingsley; van der Heyde, Mieke; Moreira-Grez, Benjamin; Valliere, Justin; Viscarra Rossel, Raphael; Wong, Wei San; Nevill, Paul; Whitely, Andy (2020)
1. Global interest in building healthy soils combined with new DNA sequencing technologies has led to the generation of a vast amount of soil microbial community (SMC) data.